The Branding of Kampung Adat Rimbo Tarok Gunung Sariak Village as a Cultural Tourism Attraction - Vernanda Em Afdhal; Stevany Stevany; Tedy Wiraseptya (Institute for Research and Community Services, 2022)
Branding is the process of building a brand to form an image or brand image. One of the thematic villages is Kampung Adat Rimbo Tarok, Gunung Sariak. This village has the potential to develop as an area that can become a thematic village in Padang City. Kampung Adat Rimbo Tarok exhibits unique characteristics, which include traditional house buildings and traditional cultural arts activities. The area of Kampung Adat Rimbo Tarok has not been significantly branded as no promotional media and information are found, and the area has not been properly managed. As a result, not many people know about the existence of this thematic village. These problems inspired the authors to conduct community service activities in this village. The community service aims to brand the village as a thematic village, a program of the local government of Padang City. The local government turns the village into a cultural tourism area. Departing from the facts described, the author intended to brand the area, starting from forming the regional brand or logo to other supporting branding media, such as an information board and other relevant media for branding design. The design stages use the 4D (four D), which is used in designing a design idea and follows stages from defining to dissemination. The expected result of these community service activities is to achieve a cultural tourism identity attached to the community, ranging from the visual identity, corporate media, and sign systems that partners or the local government can implement in local villages.